Analysis of Literature Study of Tactical Learning Approaches to Learning Outcomes of Passing and Dribbling in Soccer Skills - Dicky Tri Juniar; Krisnadiandra Krisnadiandra; Tite Juliantine; Jajat Darajat Kusuma Negara (Universitas Pendidikan Indonesia (UPI), 2021)
Learning Physical education, sport and health (PJOK - Pendidikan Jasmani Olahraga dan Kesehatan) material in big ball games, especially soccer, has several basic techniques that can be mastered such as passing and dribbling. However, students who are new to basic techniques in soccer will certainly experience difficulties. Therefore an appropriate approach is needed, one of which is a tactical approach. This approach emphasizes the activeness of students movements during the learning process. This study aims to determine the effect of applying a tactical approach to improving the learning outcomes of passing and dribbling in soccer. The application of a tactical learning approach using basic soccer skills in the game of soccer can be used in training students basic such as passing and dribbling skills, by researching through simple literature studies using literature from various journal articleÂ sources found from international and national journal sites, after finding articles journals that include and match the inclusion criteria with the researcher's research, then a matrix is made which includes the name and year of the researcher, the research results, and the important results that the researcher can use. After that, the results of the literature study will be analyzed by the researcher. The conclusion that can be obtained is that the use of tactical learning approaches in soccer skills can support physical education learning to be more effective and the application of tactical learning approaches in soccer games can affect the passing and dribbling skills of students.